2013
DOI: 10.1126/science.342.6157.415
|View full text |Cite
|
Sign up to set email alerts
|

Surprising New Dengue Virus Throws a Spanner in Disease Control Efforts

Abstract: Scientists have discovered a fifth dengue virus. The first new serotype discovered in a half century could complicate control efforts, especially the quest for a vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
180
0
23

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(204 citation statements)
references
References 0 publications
1
180
0
23
Order By: Relevance
“…A small proportion of severe cases could develop into dengue haemorrhagic fever or dengue shock syndrome, or even result in death. A fifth DENV serotype was detected in 2013 (Normile, 2013). The DENV genome contains about 11,000 nucleotide bases, which code for the three structural proteins (C, prM and E) that form the viral particles and seven other non-structural proteins (NS1, NS2a, NS2b, NS3, NS4a, NS4b, NS5) that are only found in infected host cells and are involved in viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…A small proportion of severe cases could develop into dengue haemorrhagic fever or dengue shock syndrome, or even result in death. A fifth DENV serotype was detected in 2013 (Normile, 2013). The DENV genome contains about 11,000 nucleotide bases, which code for the three structural proteins (C, prM and E) that form the viral particles and seven other non-structural proteins (NS1, NS2a, NS2b, NS3, NS4a, NS4b, NS5) that are only found in infected host cells and are involved in viral replication.…”
Section: Introductionmentioning
confidence: 99%
“…Dengue outbreaks in China were previously thought to be imported and initiated by people traveling to China from dengue-endemic areas elsewhere (4); however, recent studies suggest that dengue may now be endemic to China as well (2). The epidemiological triangle of both dengue fever and dengue hemorrhagic fever, which is the more serious form of dengue, includes hosts (humans), pathogens (one or more of five dengue virus serotypes) (5), and mosquito vectors (Aedes albopictus and Aedes aegypti) with their ecological interactions (6). The dengue outbreaks are qualitatively known to be strongly influenced by temperature (7), humidity, rainfall, and socioeconomic factors like urbanization (8).…”
mentioning
confidence: 99%
“…The infection in the farmer was initially thought to be an ordinary case of sylvatic dengue caused by DENV-4 which circulates among primates and Aedes nivalis mosquitoes in the forests of South East Asia. 3 However, when the virus was isolated and a full genetic sequence was carried out, it was observed that the virus was phylogenetically distinct from the three previous forms of sylvatic DENV-4 and bore some similarity with DENV-2. 3 In the Sarawak outbreak, only one case was admitted and the other confirmed cases were treated on an outpatient basis, thereby indicating that the disease caused by DENV-5 is mild.…”
Section: The New Virusmentioning
confidence: 98%